Building E-Waste Performance Model for Green Growth (S/O 14847) - Abd Mutalib, Hafizah; Muhammad Jamil, Che Zuriana; Mohamed, Rapiah; Shafai, Nor Atikah; Naim Nor Ahmad, Saidatul Nurul Hidayah Jannatun (UUM, 2023)
Wastes from electrical and electronic appliances (e-waste) have shown an alarming increase in this digitalization era. Therefore, the purpose of this study is to investigate the practice and performance of e-waste management in business organizations. The study also examines the impact of institutional pressures and organizational factors on firm’s e-waste management practice, and the impact of the practice on e-waste management performance. Further, the study investigates if an eco-efficiency strategy plays a significant mediating role in strengthening the impact of institutional pressure and organizational factors on e-waste management practice. Using a questionnaire survey, the study was conducted on Bursa Malaysia listed firms, specifically in the technology and telecommunication industries. The results revealed a significant impact of the organizational factors on e-waste management practice. However, the impact of institutional pressure on e-waste management practice was only found through the embedment of an eco-efficiency strategy. The study also found positive impact of e-waste management practice on e-waste management performance. The findings from this study contributes towards achieving green growth for sustainability and resilence.